Effect of Meditation on Cognitive Functions in Context of Aging and Neurodegenerative Diseases - Marciniak, Rafał; Sheardova, Katerina; Čermáková, Pavla; Hudeček, Daniel; Šumec, Rastislav; Hort, Jakub (Frontiers in Behavioral Neuroscience, 2014)
Effect of different meditation practices on various aspects of mental and physical health is receiving growing attention. The present paper reviews evidence on the effects of several mediation practices on cognitive functions in the context of aging and neurodegenerative diseases. The effect of meditation in this area is still poorly explored. Seven studies were detected through the databases search, which explores the effect of meditation on attention, memory, executive functions, and other miscellaneous measures of cognition in a sample of older people and people suffering from neurodegenerative diseases. Overall, reviewed studies suggested a positive effect of meditation techniques, particularly in the area of attention, as well as memory, verbal fluency, and cognitive flexibility. These findings are discussed in the context of MRI studies suggesting structural correlates of the effects. Meditation can be a potentially suitable non-pharmacological intervention aimed at the prevention of cognitive decline in the elderly. However, the conclusions of these studies are limited by their methodological flaws and differences of various types of meditation techniques. Further research in this direction could help to verify the validity of the findings and clarify the problematic aspects.